FACTORS IMPACTING ENGLISH AS AN ADDITIONAL LANGUAGE (EAL) TEACHING IN VICTORIAN SECONDARY SCHOOLS - Eliaser Ulimpa (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This article discusses the major challenges in the implementation of English as an Additional Language (EAL) education in secondary schools across Victoria, Australia. The background of this study is based on the increasing cultural and linguistic diversity among students, which requires the education system to provide effective and inclusive language learning services. The focus of the study is directed toward various obstacles in the implementation of EAL programs, including students’ low English proficiency, limited resources, insufficient language pedagogy competence among non-specialist teachers, and inconsistencies in educational policies and funding. This study employs a literature review method by analysing various scientific sources, academic articles, and policy documents related to EAL education in Victorian secondary schools. The research stages include literature collection, selection of relevant sources, content analysis, and synthesis of findings to identify challenges and effective strategies in EAL learning. The findings indicate that the success of EAL programs is influenced by consistent policy support, improved teacher competence, inclusive curriculum access, and learning strategies that are responsive to student diversity. The conclusion of this study emphasizes that strengthening institutional support, enhancing teachers’ professional development, and providing adequate resources are essential to improving language proficiency and academic outcomes for EAL students in secondary schools. ABSTRAK Artikel ini membahas tantangan utama dalam penyelenggaraan pendidikan English as an Additional Language (EAL) di sekolah menengah wilayah Victoria, Australia. Latar belakang penelitian ini didasarkan pada meningkatnya keberagaman budaya dan bahasa siswa yang menuntut sistem pendidikan menyediakan layanan pembelajaran bahasa yang efektif dan inklusif. Fokus kajian diarahkan pada berbagai kendala dalam pelaksanaan program EAL, seperti rendahnya kemampuan bahasa Inggris siswa, keterbatasan sumber daya, kurangnya kompetensi pedagogi bahasa pada guru nonspesialis, serta ketidakkonsistenan kebijakan dan pendanaan pendidikan. Penelitian ini menggunakan metode kajian literatur (literature review) dengan menganalisis berbagai sumber ilmiah, artikel akademik, dan dokumen kebijakan terkait pendidikan EAL di sekolah menengah Victoria. Tahapan penelitian meliputi pengumpulan literatur, seleksi sumber yang relevan, analisis isi, serta sintesis temuan untuk mengidentifikasi tantangan dan strategi efektif dalam pembelajaran EAL. Hasil kajian menunjukkan bahwa keberhasilan program EAL dipengaruhi oleh dukungan kebijakan yang konsisten, peningkatan kompetensi guru, akses kurikulum yang inklusif, serta strategi pembelajaran yang responsif terhadap keberagaman siswa. Simpulan penelitian ini menegaskan bahwa penguatan dukungan institusi, pengembangan profesional guru, dan penyediaan sumber daya yang memadai sangat penting untuk meningkatkan kemampuan bahasa dan hasil akademik siswa EAL di sekolah menengah.